Aortic Root Thrombosis on ECMO—A Novel Management Strategy. Issue 5 (September 2020) - Aljohani, Othman A.; Singh, Rakesh K.; Nageotte, Stephen J.; Do, Thomas; Ratnayaka, Kanishka; Nigro, John J.; Werho, David K.
A 15-year-old presented in cardiogenic shock secondary to viral myocarditis requiring venoarterial extracorporeal membrane oxygenation (ECMO) support. He developed large thrombi of the left ventricle and aortic root. Anticoagulation was increased, and medications were initiated to decrease the likelihood of aortic valve opening. He underwent balloon atrial septostomy followed by placement of a left atrial vent. A pigtail catheter was placed in the ascending aorta for direct heparin infusion. Serial echocardiograms showed progressive resolution of the thrombi. He was successfully weaned from ECMO and discharged home without neurological deficits.